MENELISIK MAKNA PEMBIAYAAN QARDHUL HASAN DAN IMPLEMENTASINYA PADA PERBANKAN SYARIAH DI INDONESIA - Falikhatun Falikhatun; Yasmin Umar Assegaff; Hasim Hasim (Jurnal Keuangan dan Perbankan, 2016)
ABSTRACTThis study aimed to analyze about the meaning Muqridh and Qardhul Hasan implementation on IslamicBanking in Indonesia. The paradigm used in this study is interpretive paradigm with a phenomenologicalapproach. The methods of data collection are indepth interviews, observation, and documentation, while theanalysis taken is Interpretative Phenomenological Analysis (IPA) and Syari Analysis. Interpretative Phenomenology Analysis (IPA) result shows that according to the understanding Muqridh, Qardhul Hasan hasdiverse meanings, namely Qardhul Hasan defined as loans and also interpreted as charitable. It is stated in thefinancing of implementation Qardhul Hasan is done in two ways: Productive Loan and Social Fund. Further more, according to the data presented in the Financial Statements of Islamic Banking, Qardhul Hasan fundingcomes from three sources, namely Non-Halal Funds, Fines, and Infaq Sadaqah. It is not accordance with Islamiclaw because the mix of funds derived from activities that are kosher and non-kosher (Makruh even the possibil-ity haram). To the solution offered is to change the paradigm by providing a correct understanding of thefinancing Qardhul Hasan is as charitable, and merge the Non-Halal Funds and Penalties as Corporate Social Responsibili (CSR) Funds. Suggestion of this research is mainly proposed for (1) more Islamic banks todevelop financing models Qardhul Hasan are more varied, and (2) for subsequent researchers in order todevelop research related to Hasan Qardhul contribution to alleviate poverty in Indonesia.